2015
DOI: 10.1093/eurheartj/ehv422
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of right ventricular septal pacing and right ventricular apical pacing in patients receiving cardiac resynchronization therapy defibrillators: the SEPTAL CRT Study

Abstract: AimsCardiac resynchronization therapy (CRT) is a recommended treatment of heart failure (HF) patients with depressed left ventricular ejection fraction and wide QRS. The optimal right ventricular (RV) lead position being a matter of debate, we sought to examine whether RV septal (RVS) pacing was not inferior to RV apical (RVA) pacing on left ventricular reverse remodelling in patients receiving a CRT-defibrillator.Methods and resultsPatients (n = 263, age = 63.4 ± 9.5 years) were randomly assigned in a 1:1 rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 34 publications
1
28
0
2
Order By: Relevance
“…We retrieved 82 citations from electronic database and manual searches as shown in Figure . We reviewed 16 citations for full‐text articles; 7 full‐text articles were included in the final analysis . Four of the included studies were post hoc analyses of the RCTs and one was randomized crossover trial .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We retrieved 82 citations from electronic database and manual searches as shown in Figure . We reviewed 16 citations for full‐text articles; 7 full‐text articles were included in the final analysis . Four of the included studies were post hoc analyses of the RCTs and one was randomized crossover trial .…”
Section: Resultsmentioning
confidence: 99%
“…We reviewed 16 citations for fulltext articles; 7 full-text articles were included in the final analysis. [17][18][19][20][21][22][23] Four of the included studies were post hoc analyses of the RCTs [19][20][21][22] and one was randomized crossover trial. 21 All the included studies were published between 2011 and 2016.…”
Section: Description Of Individual Studiesmentioning
confidence: 99%
“…In the REVERSE trial, no differences in a composite clinical score were observed between RV apical and nonapical lead positions 3. In the SEPTAL‐CRT (SEPTAL‐cardiac resynchronization therapy) study,19 the LV reverse remodeling response as well as total mortality or HF hospitalization were similar with RV apical and nonapical lead positions. The present study adds further evidence for a lack of influence on outcomes of RV pacing site (apical or septal) in CRT.…”
Section: Discussionmentioning
confidence: 96%
“…Early work evaluating non-apical RV pacing conducted by Khan et al [117] showed that LV remodeling rates were unaffected by RV lead position, while Kutyifa et al [118] also highlighted a higher risk of ventricular arrhythmias. The SEPTAL CRT study randomly assigned patients to receive either a septal or apical RV lead and demonstrated no significant difference in clinical outcome [119]. …”
Section: Identifying the Site Of Latest Electrical Activation (Lea)mentioning
confidence: 99%